Exercícios com jornais - Dutra, Susi Maria de Oliveira (Comunicação & Educação, 1999)
A third-grade teacher in a public school in the city of Sorocaba, São Paulo, reports on the planning and execution of a teaching experience using the newspaper in the classroom. The work was planned in four stages, starting at the level of the students' reality who, at first, need to understand how the newspaper can be handled, how it can be used for research, and how it helps one to understand local, national and international themes. The project was then continued by using the newspaper as a source of information for the disciplines in the school curriculum. Finally, together the students, a "spoken" paper was put together.